Analisis Dampak Pencemaran Limbah B3 Terhadap Perairan serta Pengelolaannya - Anggun Febrianti; Karisma Nisaatul Mufidah (Indo Publishing, 2025)
Living things are very dependent on the existence of the environment. The environment is the space inhabited by living things and affects the sustainability of living things in it. Water as one of the components in the environment which has a vital function for every living thing, especially humans. However, the environmental ecosystem can be disrupted due to pollution. One of the pollution that often occurs is pollution of waters, especially rivers. Water can be said to be polluted if it has entered contaminants that cause changes in color, taste, and smell. One type of pollutant that generally causes water pollution is B3 waste. Given the dangerous impact of hazardous waste that is not managed properly, the purpose of this study is to determine the impact of hazardous waste disposal in rivers and the proper management of hazardous waste. This research uses a normative study method by analyzing various sources regarding hazardous and toxic waste. Water pollution by B3 waste not only has an impact on the destruction of ecosystems but also has an impact on health and the environment. The adverse effects caused by B3 waste make the handling of B3 waste requires special supervision and management.